The Morphosyntax of Applicative Construction in Dawan Language - Benu, Naniana Nimrod (e-Journal of Linguistics; Vol 18 No 1 (2024): ejl-January, 2023)
This paper is aimed at analyzing the applicative construction in Dawan Language. Applicative construction used in this paper refers to the process of advancement or promoting the peripheral argument to become a core argument. This process resulted in the valence raising of the verbs, such as an intransitive becoming transitive and a transitive becoming ditransitive.  It is found that there are five types of applicative construction in Dawan language, namely benefactive, locative, recipient, instrumental, and source. Based on the analysis, it is found that there is no applicative affix in Dawan language that functions to raise or indicate a newly added argument. So, the process of raising is done through the advancement or promoting a peripheral argument to the core argument. This process of advancement then changes the role of the argument, where the oblique becomes undergoer and the undergoer argument moves to an oblique position, but not as an adjunct but as a core oblique.